Age-related cataracts and Prdx6: correlation between severity of lens opacity, age and the level of Prdx 6 expression. Issue 8 (7th May 2009) - Hasanova, N; Kubo, E; Kumamoto, Y; Takamura, Y; Akagi, Y
Abstract : Background: Peroxiredoxin 6 (Prdx6), a new family of antioxidants, regulates gene expression and function by controlling reactive oxygen species, delays hereditary cataracts in rats and protects epithelial cells in the lens against oxidative stresses. Aim: To investigate the correlation between Prdx6 expression, age and the severity of lens opacity at the time of cataract surgery. Methods: 88 cataractous eyes were examined at Fukui University Hospital, Fukui, Japan, between March 2007 and October 2007. The patient age at the time of surgery, and the subtype and severity of cataract as classified according to the modified version of the Lens Opacities Classification System version III (LOCSIII) were recorded, as well as the expression level of Prdx6 mRNA in their lenses. Results: The expression of Prdx6 was found to be significantly negatively associated with age at the time of cataract surgery (p<0.047). A significant correlation was also found between a higher nuclear or cortical cataract score and lower expression of Prdx6 in patients under 70 years old. Conclusion: These findings suggest that oxidative stress contributes to nuclear cataract formation and that a local decrease in Prdx6 in cataractous lenses may indicate the initiation of age-related cataract formation.